Left paraduodenal hernia: An overlooked cause of acute abdomen - A case report - Bhushan Shah; Jayant Bajaj; Adithya Reddy Vijendra; Devendra S. Yadav (International Journal of Abdominal Wall and Hernia Surgery)
Internal abdominal hernias are uncommon causes of intestinal obstruction, making them elusive in diagnosis. Paraduodenal hernias (PDH) represent the most common subset, accounting for up to 53% of all internal hernias. They occur due to herniation of the small bowel into the paraduodenal fossa. Symptomatology in a patient ranges from asymptomatic, chronic abdominal pain to acute abdomen. Although rare, a high index of suspicion of PDH is required to prevent its fatal complications such as bowel incarceration, volvulus, or strangulation. Preoperative evaluation with a computed tomography scan of the abdomen facilitates diagnosis and timely surgical intervention. We present a case of a 26-year-old male patient managed with an open surgical approach for a left PDH in an emergency with a good clinical outcome. This case report emphasizes the importance of awareness of this uncommon condition and its consideration in the differential diagnosis of acute abdomen to avert unnecessary hospitalization and surgery.